The IQ-1S JNK (c-Jun N-Terminal Kinase) Inhibitor Suppresses Premature Aging of OXYS Rat Brain - Zhdankina A. A. Anna Aleksandrovna; Osipenko A. N. Anton Nikolaevich; Tikhonov D. I.; Logvinov S. V. Sergey Valentinovich; Plotnikov M. B. Mark Borisovich; Khlebnikov A. I. Andrey Ivanovich; Kolosova M. G. Nataliya Gorislavovna (2023, 2023)
Title screen